Ku80 is involved in telomere maintenance but dispensable for genomic stability in Leishmania mexicana - Poláková, Ester; Albanaz, Amanda T S; Zakharova, Alexandra; Novozhilova, Tatiana S; Gerasimov, Evgeny S; Yurchenko, Vyacheslav (PLoS neglected tropical diseases, 2021)
BACKGROUND: Telomeres are indispensable for genome stability maintenance. They are maintained by the telomere-associated protein complex, which include Ku proteins and a telomerase among others. Here, we investigated a role of Ku80 in Leishmania mexicana. Leishmania is a genus of parasitic protists of the family Trypanosomatidae causing a vector-born disease called leishmaniasis. METHODOLOGY/PRINCIPAL FINDINGS: We used the previously established CRISPR/Cas9 system to mediate ablation of Ku80- and Ku70-encoding genes in L. mexicana. Complete knock-outs of both genes were confirmed by Southern blotting, whole-genome Illumina sequencing, and RT-qPCR. Resulting telomeric phenotypes were subsequently investigated using Southern blotting detection of terminal restriction fragments. The genome integrity in the Ku80- deficient cells was further investigated by whole-genome sequencing. Our work revealed that telomeres in the ΔKu80 L. mexicana are elongated compared to those of the wild type. This is a surprising finding considering that in another model trypanosomatid, Trypanosoma brucei, they are shortened upon ablation of the same gene. A telomere elongation phenotype has been documented in other species and associated with a presence of telomerase-independent alternative telomere lengthening pathway. Our results also showed that Ku80 appears to be not involved in genome stability maintenance in L. mexicana. CONCLUSION/SIGNIFICANCE: Ablation of the Ku proteins in L. mexicana triggers telomere elongation, but does not have an adverse impact on genome integrity.
Keywords: Protozoan Proteins; Ku Autoantigen; Leishmania mexicana; Leishmaniasis, Cutaneous; lidé; nestabilita genomu; protozoální proteiny; leishmanióza kožní; Genomic Instability; Humans; Genome, Protozoan; antigen Ku; Trypanosoma brucei brucei; telomery; Telomere; genom protozoální